Pengaruh Situation Awareness terhadap Peningkatan Task Performance Bidan Desa - Sendy Ayu Mitra Uktutias; Cholichul Hadi (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2023)
The strategy to reduce the high infant mortality rate (IMR) is by placing midwives in the village. One of the tasks of village midwives is the prevention of complications through early detection, which is indicated by the performance of midwives based on neonatal coverage. Situation awareness is an important component of decision making that has a significant impact on the performance of the village midwife's duties, so the purpose of this study was to analyze the effect of the role of situation awareness on the performance of the village midwife's duties in detecting problems in young infants. Quantitative research was designed using a cross sectional study. All village midwives became the population and were determined based on the results of a sample calculation of 151 village midwives who would be taken proportionally. The research variables were situation awareness and task performance. The instrument used a questionnaire and analyzed using Simple Linear Regression. The results explained that the consistent value of task performance was 43.041. B situation awareness value (regression coefficient) 0.917. The regression coefficient is positive that the direction of the influence of situation awareness on task performance is positive. Decision making in simple linear regression is 0.000 <0.05 with the t value showing 8.256> from the t table of 1.97, which means that situation awareness has an influence on the performance of the village midwife's duties. Situation awareness is a predictor that is able to influence task performance for village midwives in providing care to neonates in early detection of problems in young infants.